Change Leadership in Higher Education: Exploring of Theories and Practices - Saifaldin Idris Onia (International Journal of Multidisciplinary Approach Research and Science, 2025)
Change leadership in higher education institutions is very interesting and has been the topic of the scholars worldwide. This paper aimed to shed light on the concept of change leadership, related models and theories of change leadership practices in higher education. This paper is purely a qualitative research where selected papers are reviewed. The selected papers to be reviewed are gathered through extensive literature review from academic papers representing an output of previous studies conducted by various researches concerning change leadership practices in higher education institutions. These studies have been published in relevant websites over the Internet, which include scientific publications, periodicals, studies, scientific research. The paper concludes that higher education institutions need change leaders who have the confidence to adjust an organization's focus. There are several models and theories of change leadership. In this paper three models were reviewed; the Lewin’s model of change, Dunphy and Stace’s model, and Kotter’s model. Lewin theorized a three stage model of change as unfreezing, change, and refreeze. Dunphy and Stace incorporate participatory evolution forced evolution, charismatic transformation, and dictatorial transformation. Kotter’s model proposed eight steps in the change process. The eight steps classified into three phases: create a climate for change, engage and enable the whole organization, and implementing and sustaining Change. Hence, higher education institutions need change leaders who have the confidence to adjust an organization's focus, and who have the leadership skills to make sweeping changes in an organization by moving people or groups in a general direction.